(untitled) (Italian Journal of Public Health, 2012)
Geoffrey Rose, in his article “Sick individuals and sick populations” highlighted the need to distinguish between prevention for populations and prevention for high risk individuals. In this article we revisit some of these concepts in light of the burgeoning literature on “personalised medicine” and of findings from our investigations into personalised cancer prevention as part of an EU research gene-environment study on hormone related cancers, the Collaborative Oncological Gene- environment Study (COGS). We suggest that Rose’s high risk strategy may be modified by segmenting the population by risk (in our example genetic risk) into a number of individual strata, to each of which differential interventions may be applied. We call this “stratified prevention”, and argue that such an approach will lead to consequential advantages in efficiency, effectiveness and harm minimisation.